1982
DOI: 10.1295/polymj.14.517
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Hydrodynamic Properties of Cellulose Diacetate–Dimethylacetamide Solutions

Abstract: ABSTRACT:Viscometric and light scattering investigations were carried out on cellulose diacetate (degree of substitution, DS = 2.46) in dimethylacetamide (DMAc) at 25cC. The following molecular weight dependence of limiting viscosity number [17] Cellulose acetate (CA) with different degrees of substitution (DS) constitute a series of polymers whose molecular properties have not been systematically explored, mainly because of the experimental difficulty in removing gel-like materials from the solutions. Consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Dilute-solution data for CA in DMAc have been reported by Kamide et al11,12 These reveal no aggregation effects of the type observed for cellulose.3 However, association effects in relatively concentrated solutions have not been investigated.…”
mentioning
confidence: 99%
“…Dilute-solution data for CA in DMAc have been reported by Kamide et al11,12 These reveal no aggregation effects of the type observed for cellulose.3 However, association effects in relatively concentrated solutions have not been investigated.…”
mentioning
confidence: 99%
“…Here we used 0.504 X 10-8 (em) for Ar. 13 These values of a and C ro indicated that CA (DS= 1.75) is stiffer than CA (DS=0.49) and CA (DS=2.92), but more flexible than CA (DS = 2.46), on making a comparison of all these polymers in DMAc. We found by NMR and ultrasonic interferometer measurements that solvation occurs in DMAc solutions of CA (DS=0.49), CA (DS=2.46), and CA (DS=2.92) and that this solvation contributes mainly to the chain rigidity of cellulose acetate in DMAcP Therefore, it may be concluded that the difference in equilibrium chain rigidity among CA with different DS is a reflection 252 of the difference in degree of solvation.…”
Section: Resultsmentioning
confidence: 92%
“…75. From its 13 C NMR spectra in deuterated dimethylsulfoxide (DMSO-d 6 ), the average probabilities that the hydroxyl groups attached to the C2 , C3 , and C6 atoms were substituted by the 0-acetyl groups, i.e., ! {,_f 6 'J; were estimated to be 0.45, 0.54, and 0.76, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 8 shows the relation between and db for a CA (2.46) sample (EF3-15) in DMAc. 19 In the range dbz5 X lO-S em, is almost independent of db. As shown in Table I concluded that is insensitive to db.…”
Section: Miscellaneamentioning
confidence: 94%
“…The friction constant (w per unit length of the wormlike cylinder is assumed to be equal to (P per unit length of the pearl necklace chain, i.e., (19) Ullman 7 derived a relation between (wand [YJ] for the wormlike cylinder with a finite cross section (see Figure lc), i.e., (20) with (21) Here, Wi is the weight associated with variable xi in the Gaussian quadrature formulas; k is a hydrodynamic interaction parameter corresponding to the draining parameter X for the pearl necklace chain, and cp(xi, x) is a dimensionless quantity proportional to the torque of the hydrodynamic force acting on a point of the wormlike cylinder. The equations in the Appendix of ref 7 12 hydroxyethyl cellulose (HEC) (l)jwater, 29 ethyl hydroxyethyl cellulose (EHEC)/water, 30 sodium carboxymethyl cellulose (NaCMC) (0.88)/aq NaCl (at the limit of infinite ionic strength, i.e., /-HY:J).…”
Section: Evaluation Of the Diameter Db'mentioning
confidence: 99%